Clean production of new functional coatings of magnetic nanoparticles from sustainable resources. (10th February 2019) - Nan, Alexandrina; Filip, Xenia; Dan, Monica; Marincaş, Olivian
Abstract: Magnetic nanoparticles coated with functional polymers play an important role in clean ways of catalysis and water treatment as well as in nanomedicine. Known systems either contain only terminal functions or polymers with pendant positively charged groups. Poly(tartaric acid) (PTA) as a new polymer with multiple pendant negatively charged carboxylate groups was pursued useful for coating magnetic nanoparticles. Simple heating of tartaric acid as a sustainable natural product without using a solvent or a catalyst under controlled conditions leads to poly(tartaric acid). The reaction runs in the solid state by elimination of water and traces of carbon oxides. The structure of the resulting poly(tartaric acid) consists mainly of polyester moieties with pendant carboxyl groups and some lactide units. It was elucidated by mass spectrometry, solid-state 13 C nuclear magnetic resonance ( 13 C ss -NMR) and Fourier-transform infrared spectroscopy (FTIR). The properties of the products depend in part on the type of starting materials ( L -tartaric acid or D, L -tartaric acid). Pendant carboxyl and hydroxyl groups provide hydrophilicity and the possibility to link functions of interest. The PTA was used as new functional coatings for magnetite nanoparticles in a clean way by mixing the components and magnetic separation. The chemical stability of the magnetic nanoparticles covered by PTA was studied by UV-VIS spectroscopy in water for three weeks. Further linkage of amino-containing entities of practical interest was demonstrated by covalently binding of glucosamine. Graphical abstract: Highlights: Polymerized natural tartaric acid is a new coating for magnetic nanoparticles. Poly(tartaric acid) is obtained in a green way avoiding solvents and catalysts. Easy synthesis of poly(tartaric acid) using natural sustainable resources. During polymerization water is formed as by-products.